TRAINING INTENSITY OF MUSCLE POWER (Fiep Bulletin - online, 2013)
Several sports require movements performed at high velocity against a resistance, as kicks, throws and jumps, where muscle power is determinant for a good performance. Faced with the quest for an improved in sport performance, the challenge arises on the decision of the training intensity of muscle power, that requires the analysis of the relationship between strength and speed. The aim of this study was to dissert on important aspects in the selection intensity for the production and training of power, through a literature review. It was concluded that training that privileges the speed should be used in specific phase of training, while privileging the strength should be applied in basic period. Still, the combination of these methods can generate gains in less time.
Keywords: Muscle Power; training; intensity